Nuclear envelope attachment of telomeres limits TERRA and telomeric rearrangements in quiescent fission yeast cells. Issue 6 (25th January 2020) - Maestroni, Laetitia; Reyes, Céline; Vaurs, Mélina; Gachet, Yannick; Tournier, Sylvie; Géli, Vincent; Coulon, Stéphane
Abstract: Telomere anchoring to nuclear envelope (NE) is a key feature of nuclear genome architecture. Peripheral localization of telomeres is important for chromatin silencing, telomere replication and for the control of inappropriate recombination. Here, we report that fission yeast quiescent cells harbor predominantly a single telomeric cluster anchored to the NE. Telomere cluster association to the NE relies on Rap1–Bqt4 interaction, which is impacted by the length of telomeric sequences. In quiescent cells, reducing telomere length or deleting bqt4, both result in an increase in transcription of the telomeric repeat-containing RNA (TERRA). In the absence of Bqt4, telomere shortening leads to deep increase in TERRA level and the concomitant formation of subtelomeric rearrangements (STEEx) that accumulate massively in quiescent cells. Taken together, our data demonstrate that Rap1–Bqt4-dependent telomere association to NE preserves telomere integrity in post-mitotic cells, preventing telomeric transcription and recombination. This defines the nuclear periphery as an area where recombination is restricted, creating a safe zone for telomeres of post-mitotic cells.